2020
DOI: 10.1557/jmr.2020.220
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of calcium–magnesium–aluminum–silicon oxide mitigation in selected self-healing thermal barrier coating ceramics

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The CMAS sand was obtained from a commercial source (AFRL-02 test dust, PTI Inc., Arden Hills, MN, USA). Composition analysis of the CMAS sand revealed that it comprised 34% quartz, 30% gypsum, 17% aplite, 14% dolomite, and 5% salt; the DSC/DTA scans data showed that the melting temperature was 1150~1200 • C [29]. The sand was mixed with alcohol to form a slurry and was then brushed evenly over the surfaces of the TBC samples at a controlled dosage of 35 ± 2 mg/cm 2 .…”
Section: Cmas Corrosion Testmentioning
confidence: 99%
“…The CMAS sand was obtained from a commercial source (AFRL-02 test dust, PTI Inc., Arden Hills, MN, USA). Composition analysis of the CMAS sand revealed that it comprised 34% quartz, 30% gypsum, 17% aplite, 14% dolomite, and 5% salt; the DSC/DTA scans data showed that the melting temperature was 1150~1200 • C [29]. The sand was mixed with alcohol to form a slurry and was then brushed evenly over the surfaces of the TBC samples at a controlled dosage of 35 ± 2 mg/cm 2 .…”
Section: Cmas Corrosion Testmentioning
confidence: 99%